2022
DOI: 10.1177/13623613221103699
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind in naturalistic conversations between autistic and typically developing children and adolescents

Abstract: Successful social interactions are assumed to depend on theory of mind—the ability to represent others’ mental states—yet most studies of the relation between theory of mind and social-interactive success rely on non-interactive tasks that do not adequately capture the spontaneous engagement of theory of mind, a crucial component of everyday social interactions. We addressed this gap by establishing a novel observational rating scale to measure the spontaneous use of theory of mind (or lack thereof) within nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 93 publications
(112 reference statements)
1
16
0
Order By: Relevance
“…In fact, no individual trait or task social cognitive measures reached a BF commensurate with moderate evidence against the null hypothesis. This is consistent with previous work which has not shown a positive association between theory of mind ability and self-or partnergenerated ratings of interaction quality (Alkire et al, 2022). It is likely that casual introductory social interactions do not require good mind-reading skills in order to be successful, especially if the success measure is subjective quality rather than task-based performance, which more overtly requires communicative understanding.…”
Section: Social-cognitive Ability Does Not Predict Subjective Interac...supporting
confidence: 90%
See 1 more Smart Citation
“…In fact, no individual trait or task social cognitive measures reached a BF commensurate with moderate evidence against the null hypothesis. This is consistent with previous work which has not shown a positive association between theory of mind ability and self-or partnergenerated ratings of interaction quality (Alkire et al, 2022). It is likely that casual introductory social interactions do not require good mind-reading skills in order to be successful, especially if the success measure is subjective quality rather than task-based performance, which more overtly requires communicative understanding.…”
Section: Social-cognitive Ability Does Not Predict Subjective Interac...supporting
confidence: 90%
“…Empirical findings reveal modest links between social cognitive traits and outcomes such as relationship quality and maintenance (Gleason et al, 2009;Lecce et al, 2017;Nilsen & Bacso, 2017;Sened et al, 2017). However, there is a good deal of disconnect between examining socialcognitive ability through trait assessments or laboratory tasks and how social interactions unfold naturally (Alkire et al, 2022;Zaki et al, 2008). Dynamic interactions provide rich verbal and nonverbal information directly to the interaction partner, and in turn require reciprocal information from them.…”
mentioning
confidence: 99%
“…It should be noted though that all aforementioned studies, despite their findings, did not use in vivo measures of social functioning or a naturalistic context of assessment. Social skills finally have been theoretically proposed to also depend on social cognition aspects such as mental state/emotion recognition [23] but these aspects are not consistently associated with social impairment in ASD [24]. Given these potential associations among social cognition and social skills, EF and social skills, and EF and social cognition (e.g., [25], [26]), it has been suggested that EF may contribute to social skills both directly and indirectly [27]; Social cognition aspects are likely to partially mediate the association between EF and social skills.…”
Section: Social Skills and Executive Functions In Asdmentioning
confidence: 99%
“…With regards to the mental state/emotion recognition ability, it was not found significantly related to performance in VR social scenarios but associated only with computing and gaming experience variables. Previous evidence suggests that individuals with ASD present difficulties in recognition of mental states/emotions (e.g., [104]- [106]), but there are limited and inconsistent findings regarding its association with social competence (e.g., [24]). Our results showed that in adults with ASD, plausibly, it is other cognitive functions (such as EF) that are implicated in the expression of social skills.…”
Section: Mental State/emotion Recognitionmentioning
confidence: 99%
“…It should be noted though that all aforementioned studies, despite their findings, did not use in vivo measures of social functioning or a naturalistic context of assessment. Social skills finally have been theoretically proposed to also depend on social cognition aspects such as mental state/emotion recognition [25] but as these aspects are not consistently associated with social impairment in ASD [26], the extent to which socio-cognitive abilities associate with the social difficulties in ASD has been debated over the years. Given these potential associations among social cognition and social skills, EF and social skills, and EF and social cognition (e.g., [27]- [29]), it has been suggested that EF may contribute to social skills both directly and indirectly [30].…”
Section: Social Skills and Executive Functions In Asdmentioning
confidence: 99%